Optimization of Customer Satisfaction as a Bridge to Loyalty in Student Boarding House Business around Bahaudin Mudhary University - Rahmatika, Ferizka; Hidayat, Rachmad; Rahayu, Sri; Fitrianty, Rifda (Majapahit Journal of Islamic Finance and Management, 2025)
This study aims to analyze the influence of CRM and Perceived Value on customer loyalty in boarding houses around Bahaudin Mudhary University, Madura. The research was motivated by the need to foster customer loyalty in the competitive student housing industry. A quantitative method was employed using Partial Least Squares-Structural Equation Modeling (PLS-SEM) analysis. Data were collected through questionnaires distributed to boarding house residents near the campus. The results indicate that CRM has a significant effect on customer loyalty, whereas Perceived Value does not significantly influence either loyalty or customer satisfaction. These findings imply that relational approaches are more critical than economic considerations in maintaining boarding house tenants. The synthesis of the discussion confirms that the research objective has been achieved by identifying CRM as a key strategy in fostering tenant loyalty. The policy implication is that boarding house managers should implement structured CRM systems, supported by customer management and service communication training, with active involvement from educational institutions or local governments to promote relational-based boarding service standards.